Legal Implications of the Use of Deepfake in Politics and National Security in Indonesia - Lianingsih, Nestia; Jaizul, Alim (International Journal of Humanities, Law, and Politics, 2025)
Deepfake technology has developed rapidly and has had a significant impact in various fields, including politics and national security. This study analyzes the legal implications of the use of deepfakes in politics in Indonesia, highlighting regulatory challenges, the effectiveness of technology detection, and its impact on public opinion. This study uses a mixed methods approach, combining literature analysis, case studies, interviews with legal and technology experts, and social media data analysis. The results show that the spread of deepfakes has increased sharply ahead of the 2024 General Election, especially on Twitter, Facebook, and TikTok, contributing to disinformation and public polarization. Existing regulations, such as the Electronic Information and Transactions Law (UU ITE) and the Criminal Code (KUHP), do not specifically regulate deepfakes, thus creating difficulties in law enforcement. In addition, existing detection technologies still face challenges in identifying increasingly sophisticated deepfake content. As a mitigation measure, this study recommends the formation of special regulations regarding deepfakes, improving detection technology through collaboration with the technology sector, increasing the capacity of law enforcement in digital forensics, and public education to improve digital literacy. It is hoped that these steps can reduce the negative impact of deepfake on democracy and national security stability in Indonesia.